Mineral levels in lactating Lagos women: blood-breast milk correlation and environmental-nutritional influences - Oluwakemi Oyelowo; Christian Makwe; Abdullahi Adejare; Oyinkansola Ajulo; Cynthia Dieobi (Universa Medicina)
Background